The Importance of Reconstructing Criminal Liability for Prostitution in the Reform of Criminal Law - Itok Dwi Kurniawan (Recht Studiosum Law Review, 2024)
The practice of prostitution is currently evolving rapidly, primarily driven by the dissemination of information through electronic media. The lack of comprehensive regulations regarding prostitution allows the law to contribute to the development of this phenomenon. Insufficient regulation has created a new legal culture among those involved in prostitution, which has widespread effects on society. One of the most severe consequences of the widespread practice of prostitution is the spread of sexually transmitted diseases, which can impact the health of both those directly involved and individuals nearby, such as the partners of sex workers. This research aims to analyze the regulation of prostitution in Indonesia's criminal law today. Through this analysis, the importance of reforming the law to comprehensively regulate prostitution in the future is highlighted. The method used in this research is legal research with a normative approach, utilizing secondary data obtained through literature review and examination of legislation. The analytical method applied is prescriptive analysis. The findings indicate that although some regional regulations have addressed prostitution practices, there is no national regulation that explicitly governs prostitution. Recommendations for the future include providing a clear definition of prostitution, criminalizing consumers or users of prostitution services, criminalizing sex workers, reformulating offenses for pimps, implementing a double track system for sanctions, increasing criminal penalties, and clarifying the formulation of offenses. Keywords: reconstruction, prostitution, criminal law.